DAYA TERIMA DAN NILAI GIZI FORMULA POMPOM POTATO SEBAGAI PEMBERIAN MAKANAN TAMBAHAN BALITA STUNTING - Nur Fathin Sholihah; Rany Adelina (Media Gizi Pangan, 2021)
Stunting is a condition of height that is not suitable for the child's age due to malnutrition for a long time starting from the fetal stage to the first 2 years of life. The determinant factors of stunting include energy, protein, and zinc intake. There is a significant result of the consumption of fish on the incidence of stunting. It is necessary to develop a formula based on fish that has high nutritional value, energy, and protein which is preferred for toddlers. This research is an experimental study to determine the acceptance of the best pompom potato formula with the addition of tuna fish, comparing the macronutrient content and the recommended portion of the best pompom potato consumption. The result of developing the best of pompom potato formula is P1 (71% potato and 29% tuna). The nutrient content of energy, protein, carbohydrates, and fat per 100 g of P1 is higher than the original Potato balls recipe and lower than P2. The recommended consumption portion of P1 4 piecies is a 1-time snack.